Sintesis Bioplastik dari Tongkol Jagung sebagai Active Packaging yang Ramah Lingkungan - Umi Fathanah; Hesti Meilina; Fitria Febriani; Fatiha Rizky Utami (Jurnal Inovasi Ramah Lingkungan, 2022)
Corncob is a source of starch, used as raw material packaging which environmentally friendly, so need to be investigated. This study was to characterize bioplastic from material chitosan, starch with the addition of glycerol as plasticizer. The effects of chitosan biopolymers and glycerol plasticizers were investigated to produce bioplastics with physical and mechanical properties, which resemble to commercial plastics. Research studies include the influence of process variables on the manufacture of bioplastics made from corncob from industrial solid waste. The variables were varied are ratio starch from corncob with chitosan and glycerol. Bioplastic is made from ratio chitosan and corncob waste with variation of 0:10; 1: 9; 2: 8; 3: 7; and 4: 6 v / v with glycerol of 0, 1 and 5% of starch solution mass. Success of making biodegradable plastics from the quality of bioplastics by physical tests, mechanical tests, SEM, and FTIR. Then followed by tests of biodegrability to the environment. The best results were obtained in bioplastic samples with chitosan and starch ratio of 2: 8 v / v with the addition of 0% glycerol. Tensile strength was 10.49 MPa, elongation of break was 31.73%, Young Modulus was 2.88 MPa, swelling was 46.91%, the density was 0.31g /mL, and the bioplastics degraded perfectly in 18 days.